Influence of particle size on the mechanical properties and magnetocaloric effect of La0.8Ce0.2(Fe0.95Co0.05)11.8Si1.2/Sn composites - Zhong, Xi Chun (2020)
The particle size dependence of the mechanical properties and the magnetocaloric effect (MCE) in La0.8Ce0.2(Fe0.95Co0.05)11.8Si1.2/Sn composites were studied. The compressive strength (σbc) was in the range of 180–200 MPa for composites with particle sizes less than 180 μm, which is much higher than the compressive strength of larger size powders (136 MPa). When the particles were larger than 45 μm, the observed maximum magnetic entropy change (−ΔSM)max of 7.66–7.99 J/(kg⋅K) shows that surface/interface anisotropy effects have a negligible impact on MCE. The adiabatic temperature change (ΔTad) increased from 1.74 K@1.4 T, for particles in the size range of 0–45 μm, to 1.91 K@1.4 T for particles in the size range of 45–100 μm. The ΔTad was in the range of ∼2.0 K@1.4 T when the particle size increased from 100 to 250 μm. Magnetic hysteresis in these second-order phase transition alloys showed negligible change in the particle size range of 0–250 μm. These results are useful of La(Fe,Si)13-based compounds for magnetocaloric applications.